Sustainable Urban Planning: A Holistic Approach to Balancing Environmental Conservation, Economic Development, and Social Well-being - Yunita Sopiana; Muhammad Ade Kurnia Harahap (West Science Interdisciplinary Studies, 2023)
This research explores sustainable urban planning in Bandung City, focusing on a holistic approach that balances environmental conservation, economic development, and social welfare. The research examines existing urban planning practices, identifies environmental conservation challenges, evaluates economic development impacts, examines social welfare implications, and proposes a holistic approach to sustainable urban planning. The research utilized a mixed methods approach, including interviews, surveys, observations, and secondary data analysis. The findings of this study highlight the need to integrate environmental considerations into urban planning, address challenges such as pollution and land degradation, balance economic growth with sustainability, and promote social inclusiveness. The proposed holistic approach emphasizes compact land use, sustainable transportation, effective waste management, social inclusiveness, and community participation. By adopting this approach, Bandung City can strive to realize a more sustainable and livable urban environment.